Forest management interventions affect the trade-offs of multiple vegetation and soil ecosystem services in walnut forests in the Taihang Mountains, China - Xin Li; Yanmei Chen; Qianyuan Liu; Yanan Liu (Global Ecology and Conservation)
Artificial forests provide various ecosystem services (ESs) and contribute to mitigating global climate change. However, the differences and trade-offs among ESs under different interventions remain unclear. This study investigated the variations in ESs and their trade-offs in artificial walnut forests in the Taihang Mountains under four human interventions: original shrub-grassland, long-term unmanaged walnut forests, walnut forests with clearing of shrubs and grasses, and walnut forests with clearing of shrubs and grasses and application of fertilizers. These interventions were established after a walnut plantation on shrub-grass-dominated slopes in 2003. Four ESs were evaluated using the entropy weight method: maintenance of plant diversity, carbon sequestration, soil and water conservation, and soil nutrient maintenance. Trade-offs among ESs were analyzed using the root mean square deviation (RMSD). Results showed that: (1) both the ESs composite value and the average trade-off value between ESs initially increased, then decreased, with increasing human intervention. The highest ESs composite value (ESs = 0.5655) and the lowest average trade-off value (RMSD = 0.149) were observed in walnut forests with clearing of shrubs and grasses. (2) Most paired ESs exhibited moderate or high trade-offs with each other, but differences existed between the walnut forests and the original shrub-grassland. The original shrub-grassland showed lower trade-offs between maintenance of plant diversity and carbon sequestration, and between maintenance of plant diversity and soil nutrient maintenance, while these trade-offs increased after the conversion to walnut forests. (3) Redundancy analysis and Pearson correlation analysis revealed that aboveground biomass explained 63.9 % of the variation in ESs indicators in the walnut forests, and soil phosphorus storage was significantly correlated with the trade-offs between most paired ESs, indicating significant influences of vegetation and soil factors on ESs indicators and trade-offs. Our findings suggest that shrub and grass removal is a key intervention affecting ecosystem trade-offs in artificial forests. Therefore, effective management of plantation vegetation is necessary to support the multifunctional balance of ESs and promote plantation ecosystem stability.